Extraction of Polyphenol From Turmeric (Curcuma longa), Red Ginger (Zingiber officinale), and Aromatic Ginger (Kaempfeiria galanga l) Using Natural Deep Eutectic Solvent Based On Choline Chloride and Sugar - Maulia, Gina; Maimulyanti, Askal; Nurhidayati, Isna; Mellisani, Bella; Nurhasanah, Nurhasanah (UIN Syarif Hidayatullah Jakarta, 2025)
Indonesia is a tropical country rich in biodiversity, including a wide variety of herbal plants. Herbs and spices are abundant in Indonesia and have been used in local customs since ancient times. Turmeric, ginger, and curcuma are rhizomes used as spices in Indonesian cooking and natural medicine. This study investigates the efficiency of natural deep eutectic solvents (NADES) synthesized from choline chloride and various sugars—fructose, glucose, maltose, and xylose in extracting polyphenolic compounds from Indonesian rhizomes: turmeric (Curcuma longa), red ginger (Zingiber officinale), and aromatic ginger (Kaempferia galanga L). The NADES were prepared using choline chloride as hydrogen bond acceptor (HBA). The hydrogen bond donor (HBD) is a sugar such as fructose, xylose, maltose, and glucose. The total phenolic content (TPC) was quantified and reported in mg gallic acid equivalent (GAE)/g extract. Kaempferia galanga exhibited the highest TPC among the rhizomes, reaching 32.21 mg GAE/g when extracted with ChCl–Fructose NADES. Curcuma longa and Zingiber officinale yield 20.05 mg GAE/g and 25.84 mg GAE/g under the same solvent conditions, respectively. When comparing the performance of the solvents, the following order was observed: ChCl–Fr > ChCl–Xyl > ChCl–Mal > ChCl–Glu. These findings suggest that solvent polarity and hydrogen bonding capacity significantly influence polyphenol solubility and extraction efficiency. NADES based on ChCl–Fructose showed the greatest potential for eco-friendly extraction of bioactive phenolics from medicinal rhizomes.